ECONOMETRICS OF HEALTHCARE WORKERS' PRODUCTIVITY DETERMINANTS WITHIN THE FRAMEWORK OF INCLUSIVE HEALTH TRANSFORMATION - Azhari, Sri Rahayu Indah; Safitri, Ari Sarwo Indah; Irma, Irma Qirani (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
Global health transformation toward inclusive and sustainable healthcare services faces significant challenges regarding productivity disparities among healthcare workers between urban and rural areas. This study aims to analyze the determinant factors of healthcare worker productivity using econometric models within the framework of inclusive health transformation in underserved areas. This cross-sectional quantitative research involved 32 healthcare workers from four Primary Health Centers (Bumbu, Binanga, Keaang, and Tarialu) in West Sulawesi, selected through purposive sampling with a minimum one-year work experience criterion. The research instrument utilized a validated structured questionnaire with a 1-4 Likert scale. The variables examined included work environment (X1), discipline factors (X2), and technology support as moderating variables, with work productivity and performance effectiveness as dependent variables. Analysis employed Structural Equation Modeling (SEM) using PLS. The results demonstrated strong model validity with R-square values of 92.3% for work productivity and 83.4% for performance effectiveness. Work discipline showed a significant positive effect on performance effectiveness (coefficient 1.117, p<0.05), while work environment exhibited a non-significant negative effect on productivity (coefficient -0.058, p>0.05). Technology support revealed opposing moderation paradoxes in both examined relationships. This research unveils the technology paradox phenomenon in inclusive health transformation and confirms work discipline as the primary driver of healthcare worker performance effectiveness, with important implications for more nuanced health technology implementation strategies.